2022
DOI: 10.3389/fnut.2022.745624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Extracts From Ganoderma resinaceum on Sleep in Mice Using Combined Transcriptome and Metabolome Analysis

Abstract: Ganoderma resinaceum is a valuable Chinese medicine. This study aimed to investigate whether a G. resinaceum alcohol extract (GRAE) improves sleep, and analyze the potential mechanism. After 30 days of continuous administration of GRAE at various doses, GRAE (1,000 mg/kg.bw) prolonged pentobarbital sodium-induced sleep, increased the rate of sleeping in mice treated with a subthreshold dose of pentobarbital sodium, and shortened sleep latency. The mice brain was analyzed using UPLC-MS/MS and RNA-sequencing. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The QC sample aggregation, untreated control (CK), and treated (T) sample points were clustered closely, indicating that the sample was reliable. The cross‐validation of the PCA model mainly refers to parameters such as R2X, which explains the ability of the model 36 . The R2 of the positive and negative ion modes (R2 > 0.5) indicated that the model had a high cumulative interpretation rate and was suitable for PCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QC sample aggregation, untreated control (CK), and treated (T) sample points were clustered closely, indicating that the sample was reliable. The cross‐validation of the PCA model mainly refers to parameters such as R2X, which explains the ability of the model 36 . The R2 of the positive and negative ion modes (R2 > 0.5) indicated that the model had a high cumulative interpretation rate and was suitable for PCA.…”
Section: Resultsmentioning
confidence: 99%
“…The cross-validation of the PCA model mainly refers to parameters such as R2X, which explains the ability of the model. 36 The R2 of the The data represent mean ± SD values (n = 3). Values that do not share common lettering are significantly different (P < 0.05).…”
Section: Metabolome Data Validity and Reliabilitymentioning
confidence: 99%
“…The principal medications used to treat sleep disorders, benzodiazepines, work primarily on the central nervous system, and prolonged usage can lead to tolerance and dependency. 88,89 Hence to improve sleep quality, a safe and effective alternative is required. Modern pharmacology suggests that changes in the gut microbiota may be linked to sleep via the gut-brain axis.…”
Section: Prebiotic Impact Of G Lucidum On Sleep (Gut Microbiotadepend...mentioning
confidence: 99%